The Historical Criticism and Causality in The Philosophy of History: Ibn Khaldun’s Perspective - Muhammad Faqih Nidzom; Fiqhi Akbar Rafsanjani (TSAQAFAH, 2022)
This study will reveal how ibn Khaldun's philosophy of history, especially on his historical criticism and the concept of causality. This research is based on literature and qualitative research that uses a philosophical approach to explain the meaning of philosophy of history. This research presented Ibn Khaldun's criticism on historians' subjectivity in observing history. He believed that history progressed in the spiral pattern that moved repetitively, but the repetition continued towards progression. According to Ibn Khaldun, history is under the laws that control it, and the historical reality is a unity, not independent, and has a relationship with each other. To know the nature of civilization, all the needs to do is know the causes, principles, and elements contained in a civilization. There are four causes make the nature of civilization; ‘umrân as material cause, daulah as formal cause, ‘ashabiyah as efficient cause, and mashâlih ‘âmmah as final cause.